2020
DOI: 10.1177/1076029620961450
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned: Using the Caprini Risk Assessment Model to Provide Safe and Efficacious Thromboprophylaxis Following Hip and Knee Arthroplasty

Abstract: Two of the more common potential complications after arthroplasty are venous thromboembolism (VTE), which includes deep vein thrombosis (DVT) and pulmonary embolus (PE), and excess bleeding. Appropriate chemoprophylaxis choices are essential to prevent some of these adverse events and from exacerbating others. Risk stratification to prescribe safe and effective medications in the prevention of postoperative VTE has shown benefit in this regard. The Department of Orthopaedic Surgery at Syosset Hospital/Northwel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…After several revisions, the Caprini score has been successfully applied for the assessment of the risk of DVT after knee/hip arthroplasty. 13 , 25 However, in an analysis of 376 knee/hip arthroplasties by Bateman et al, 26 no significant difference was observed between the Caprini scores of patients with and without postoperative DVT. Bateman et al 27 had not recognised the importance of the risk of joint arthroplasty, as all patients had been categorised as high risk, with Caprini scores ≥ 5 points.…”
Section: Discussionmentioning
confidence: 99%
“…After several revisions, the Caprini score has been successfully applied for the assessment of the risk of DVT after knee/hip arthroplasty. 13 , 25 However, in an analysis of 376 knee/hip arthroplasties by Bateman et al, 26 no significant difference was observed between the Caprini scores of patients with and without postoperative DVT. Bateman et al 27 had not recognised the importance of the risk of joint arthroplasty, as all patients had been categorised as high risk, with Caprini scores ≥ 5 points.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the a priori risk factors selected in this study, the checklist includes items such as age, tumors, and PICC lines [16]. Although the Caprini model has a greater theoretical potential to prevent VTE, it is only efficacious if patient data are conscientiously analyzed and used to create real-time adjustments [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…1 These indications may be for arterial thrombosis prevention as mentioned above or for the prevention of VTE following total hip or knee replacement 46 after a risk assessment of postoperative VTE. 47 …”
Section: Methodsmentioning
confidence: 99%
“…1 These indications may be for arterial thrombosis prevention as mentioned above or for the prevention of VTE following total hip or knee replacement 46 after a risk assessment of postoperative VTE. 47 Prevention of severe acute respiratory distress syndrome in COVID-19 disease Before the COVID-19 era, several studies were conducted to investigate the role of aspirin in preventing ARDS in at-risk patients with conflicting results. A recent meta-analysis of 6764 at-risk patients across 7 studies concluded that prior aspirin use was associated with decreased incidence of ARDS in at-risk patients, but was not associated with decreased hospital mortality.…”
Section: Prevention Of Venous Thromboembolic Events During Covid-19 Pandemicmentioning
confidence: 99%